GAMBARAN PELAKSANAAN PEMBELAJARAN SCIENTIFIC DI PENDIDIKAN ANAK USIA DINI ( PAUD ) KELURAHAN PANDAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Yesi Arifianti; Tri Umari; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study was conducted in Early Childhood Education of Kelurahan Pandau Jaya District Siak Hulu Kampar. The population in this study were teachers of Early Childhood Education of Kelurahan Pandau Jaya District Siak Hulu Kampar academic year 2015/2016 a total of 50 teachers. The sample of 20 teachers. While the sampling technique based nomogram Harry King. To uncover the implementation of the scientific techniques used questionnaires. Data were analyzed using descriptive data analysis techniques. Based on the analysis concluded: (1) Palaksanaa scientific learning in early childhood education (ECD) Kelurahan Pandau Jaya District Siak Hulu Kampar regency in the category of good scientific teaching practices already implemented measures to comply with the implementation of the scientific consisting of five aspects diataranya observing, asking, think, try and form a network (2) learning scientific aspects of observing indicators included in the category of better implementation of scientific meaning in early childhood education (ECD) Kelurahan Pandau Jaya District Siak Hulu Kampar asked indicator can be categorized either ( 3) learning scientificindikator aspects asked belongs to the category quite well mean the implementation of scientific learning in early childhood education (ECD) Kelurahan Pandau Jaya District Siak Hulu Kampar asked indicator can be categorized quite good (4) learning scientific aspects of indicators and trying to make sense of the in both categories means that the implementation of scientific learning in early childhood education (ECD) Kelurahan Pandau Jaya District Siak Hulu Kampar on indicators and trying to make sense can be categorized (5) learning scientific aspects of the indicators included in the networking category is quite good means of implementation Smiling in early childhood education (ECD) Kelurahan Pandau Jaya District Siak Hulu Kampar indicator forming networks can be categorized quite good.Keywords : Scientific Learning Implementation Overview